KAJIAN LITERATUR : PERAN LITERASI MEMBACA DALAM PEMBELAJARAN DI SEKOLAH DASAR - Listikal, Melisa; Putri Wulandari, Rahmalia; Almaghfira, Muthia; Suriani, Ari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading literacy is one of the fundamental competencies that must be possessed by elementary school students, as it plays an important role in supporting the success of the learning process. This article aims to comprehensively examine the role of reading literacy in elementary school learning through a literature review approach. The method used in this study is a literature review by analyzing various scientific sources such as national journals, books, and relevant publications within the last five years. The results of the study indicate that reading literacy has a significant contribution to improving students’ understanding of learning materials, developing critical thinking skills, and supporting language abilities. In addition, the implementation of appropriate learning strategies, such as the use of interactive media and active learning methods, has been proven to strengthen students’ reading literacy skills. Therefore, reading literacy needs to be optimally integrated into the learning process in elementary schools in order to achieve more effective and meaningful educational outcomes.